2014
DOI: 10.3109/17435390.2013.875232
|View full text |Cite
|
Sign up to set email alerts
|

Bioconcentration and metabolism of BDE-209 in the presence of titanium dioxide nanoparticles and impact on the thyroid endocrine system and neuronal development in zebrafish larvae

Abstract: Interactions between organic toxicants and nanoparticles (NPs) in the aquatic environment may modify toxicant bioavailability and consequently the toxicant's environmental fate and toxicity. Therefore, we investigated the influence of titanium dioxide NPs (nano-TiO 2 ) on deca-BDE (BDE-209; a polybrominated diphenyl ether congener) bioconcentration, metabolism and its effects on the thyroid endocrine system in zebrafish (Danio rerio) larvae. Zebrafish embryos were exposed to various concentrations of BDE-209 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(49 citation statements)
references
References 60 publications
5
42
0
Order By: Relevance
“…We observed increased T 4 and T 3 content during a 6-day exposure to BDE-209, and this result is in accordance with a previous study in zebrafish embryos/larvae exposed to BDE-209 for 6 days (Wang et al, 2014). In contrast, decreased T 4 levels were observed in zebrafish embryos/larvae exposed to BDE-209 for 14 days (Chen et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…We observed increased T 4 and T 3 content during a 6-day exposure to BDE-209, and this result is in accordance with a previous study in zebrafish embryos/larvae exposed to BDE-209 for 6 days (Wang et al, 2014). In contrast, decreased T 4 levels were observed in zebrafish embryos/larvae exposed to BDE-209 for 14 days (Chen et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the alterations in the TH levels (decrease or increase) may produce several developmental effects during larval development, especially in the CNS (Chen et al, 2012b;Wang et al, 2014). In the present study, the total T 4 and T 3 concentrations decreased in all the Pb treatment groups.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, previous studies have pointed out the enrichment of heavy metals in muscle, gills, liver, and kidney of fish (Fazio et al, 2014;Svecevicius et al, 2014;Wei et al, 2014). The NPs enhance the uptake heavy metal and organic toxicants (Baun et al, 2008;Tan et al, 2012;Wang et al, 2012Wang et al, , 2014. The previous studies also reported the enhanced uptake of toxicants in the presence of NPs, can greatly affect the toxicity of potential environmental pollutants (e.g., heavy metal and organic toxicants) Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations